Relationship between Age and the Occurrence of Depression Symptoms in Children with Acute Lymphoblastic Leukemia - Dwika Intania Riano; Ika Citra Dewi Tanjung; Ririe Fachrina Malisie; Arlinda Sari Wahyuni; Olga Rasiyanti Siregar; Rini Savitri Daulay (Indonesian Journal of Global Health Research, 2025)
In children and adolescents, depressive symptoms often presenting as irritability, anhedonia, or behavioral changes. Despite significant advancements in survival rates due to improved therapeutic protocols, the psychological burden experienced by children with ALL.Objective: To evaluate the relationship between age and the presence of depressive symptoms in children diagnosed with ALL.Methods: A cross-sectional study was done using consecutive sampling with 40 children aged from 7 to 18 years old acquired, conducted from August to October 2024 at the outpatient unit of Adam Malik Hospital, Medan. Forty children aged 7–18 years with a confirmed diagnosis of ALL were included. Depressive symptoms were assessed using the Patient Health Questionnaire-9 (PHQ-9). Categorical variables were analyzed using the chi-square test, followed by bivariate to identify significant predictors of depression.Results: Among the 40 participants, the most age group were children ≤ 10 years old (65%). A statistically significant association was found between age group and the presence of depressive symptoms (p = 0.001, OR= 33,3). Conclusions: Age is significantly associated with the severity and presence of depressive symptoms in pediatric patients with ALL. Older children were more likely to report higher levels of depression. Psychological evaluation and targeted mental health support may be especially important in older age groups.